Implementation of Maqasid Syariah in the Utilization of QRIS as a Digital Transaction Platform - Putri, Anindya Cahya; Asnaini, Asnaini; Putri, Anita Eustacia (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Background. Since 2014, Bank Indonesia has implemented a program to use digital payment instruments known as National Non-Cash Movement. Bank Indonesia has innovated by creating electronic digital financial transactions using QR Codes, which can be used as a legitimate transaction tool. Since January 1, 2020, Indonesian people can use QR Codes through server-based electronic money applications, mobile banking, or electronic wallets.Purpose. The purpose of this research is specifically to answer the question of how QRIS is used in digital transactions, whether it fulfills the principles of maqashid sharia.Method. This study uses a qualitative descriptive method, by analyzing data from various sources. The data presented is in the form of statements, by collecting data through interviews or face-to-face meetings, and documentation. This study uses primary and secondary data. Data collection techniques in this study use interviews. This study also combines literature reviews, including books, essays, and other works, to support the findings.Results. This study found that the application of Maqasid Syariah in the implementation of QRIS increases user satisfaction and there is a significant correlation between QRIS users' understanding of Maqasid Syariah and the level of QRIS adoption. This study also found that the application of QRIS in digital transactions not only increases efficiency and financial inclusion in Indonesia, but also complies with the principles of Maqasid Syariah. This shows that a strong understanding of Maqasid Syariah among users can help increase QRIS adoption, despite challenges such as cybercrime.Conclusion. The importance of education about sharia and financial technology, so that the public is increasingly exposed to and can use QRIS more, so that it can encourage sustainable and inclusive digital economic growth in society. Users who understand the principles of Maqasid Syariah are more likely to use QRIS, because QRIS simplifies digital transactions and is in line with Sharia principles such as fairness and transparency